2008
DOI: 10.1016/j.crvi.2008.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of right and left ventricular function in healthy mice by blood-pool pinhole gated SPECT

Abstract: The feasibility of blood-pool pinhole ECG gated SPECT was investigated in healthy mice to assess right and left ventricular function analysis. Anaesthetized (isoflurane 1-1.5%) adult CD1 mice (n = 11) were analyzed after intravenous administration of 0.2 ml of 550 MBq of 99m Tc human albumin. For blood-pool gated SPECT imaging, 48 ventral step and shoot projections with eight time bins per RR over 180 • with 64 × 64 word images were acquired with a small animal gamma camera equipped with a pinhole collimator o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Third, as described before, we profiled the CD1 hearts from E18.5 and P1. Considering that the CD1 strain has a low penetrance of developing cardiac phenotypes and has been mostly used to study normal heart developmental processes 27 , 48 , 49 , we also profiled heart cells in C57BL/6—a mouse strain frequently used to model heart defects 50 , 51 . We analyzed C57BL/6 mouse hearts from E9.5 to P9.…”
Section: Resultsmentioning
confidence: 99%
“…Third, as described before, we profiled the CD1 hearts from E18.5 and P1. Considering that the CD1 strain has a low penetrance of developing cardiac phenotypes and has been mostly used to study normal heart developmental processes 27 , 48 , 49 , we also profiled heart cells in C57BL/6—a mouse strain frequently used to model heart defects 50 , 51 . We analyzed C57BL/6 mouse hearts from E9.5 to P9.…”
Section: Resultsmentioning
confidence: 99%
“…99m Tclabeled red blood cells were used for blood pool imaging in ECG gated micro-SPECT, demonstrating that murine LV volume assessment is possible with high voxel and temporal resolutions (Chin et al, 2007;Goetz et al, 2008a). ECG-gated blood pool micro-SPECT measurement of right ventricular volumes was also recently demonstrated in healthy living mice (Goetz et al, 2008b).…”
Section: 2: Micro-spectmentioning
confidence: 99%
“…• Assessment of LV size, shape, mass, global mechanical function (ejection fraction, end‐systolic and end‐diastolic volumes, stroke volume, cardiac output), and wall thickening using 99m Tc‐tetrofosmin, 99m Tc‐sestamibi, 201 Tl, and 99m Tc‐red blood cells. Assessment of global mechanical function of the right ventricle (ejection fraction, end‐systolic and end‐diastolic volumes, stroke volume, cardiac output) using 99m Tc‐red blood cells (Wu et al, ; Constantinesco et al, ; Chin et al, ; Goetz et al, ,b).…”
Section: : Pre‐clinical Imaging Background Physics and Examples Of Mmentioning
confidence: 99%
“…10,11 ECG gating has been evaluated for small animal SPECT for assessing left ventricular function and has been applied in studies where new pharmaceuticals were tested. [12][13][14][15][16][17][18] Simultaneous ECG and respiratory gating has been assessed for a high-resolution (1 mm) microPET system. 19 In this study, it was found that although respiratory motion was detectable in the images, its spatial extent and duration were small, and it could therefore likely be ignored for most studies.…”
mentioning
confidence: 99%